2013
DOI: 10.7763/ijiet.2013.v3.350
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning through Wikis in Higher Education

Abstract: Abstract-Higher education institutions (HEIs) can, like any other organisation, profit from the advantages of using web 2.0 tools, as these institutions need to balance acquisition processes with learners' participation and contributions. The use of these tools in training processes can contribute to pedagogical innovation and to developing students' learning and professional skills; thus, it must be promoted. This paper presents a case study which aims to validate the desired Wiki outcomes in a teaching and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…His social-cultural learning theory originally refers to expert-novice or teacher-student interactions but it has been applied to supportive behaviors by which students can help each other in the classroom or online platform (GUERRERO, VILLAMIL, 2000;LI, ZHU, 2013;CICCONI, 2014;HADJERROUIT, 2014). Online platforms offer new opportunities to team working, for example, wiki platforms with high interactivity potential that enables users to create and edit online hypertexts easily (GOMES, SOUSA, 2013;WANG, 2014). In wiki platforms, editions and revisions can be made directly in the text and the changes can be synchronized or not.…”
Section: Competences and Skills For 21st Centurymentioning
confidence: 99%
See 2 more Smart Citations
“…His social-cultural learning theory originally refers to expert-novice or teacher-student interactions but it has been applied to supportive behaviors by which students can help each other in the classroom or online platform (GUERRERO, VILLAMIL, 2000;LI, ZHU, 2013;CICCONI, 2014;HADJERROUIT, 2014). Online platforms offer new opportunities to team working, for example, wiki platforms with high interactivity potential that enables users to create and edit online hypertexts easily (GOMES, SOUSA, 2013;WANG, 2014). In wiki platforms, editions and revisions can be made directly in the text and the changes can be synchronized or not.…”
Section: Competences and Skills For 21st Centurymentioning
confidence: 99%
“…Their conclusions attest to the fact that this resource increased students' motivation to learn English, raising student confidence and promoting socio-constructivist initiatives. According to Gomes and Sousa (2013) the development of activities on wiki platforms can contribute greatly to teamwork processes, improving self-organization, integrity and transparency. The authors used a wiki platform for online activities of the Information Systems Management course to investigate the results of using this technology in the teaching and learning process.…”
Section: Competences and Skills For 21st Centurymentioning
confidence: 99%
See 1 more Smart Citation
“…His social-cultural learning theory originally refers to expert-novice or teacher-student interactions but it has been applied to supportive behaviors by which students can help each other in the classroom or online platform (Guerrero & Villamil, 2000;Li & Zhu, 2013;Cicconi, 2014;Hadjerrouit, 2014). Online platforms offer new opportunities to work in groups, such as, wiki platforms with high interactivity potential that enables users to create and edit online hypertexts easily (Gomes & Sousa, 2013;Cheuk-Hang & Wei, 2014;Wang, 2014). Editions and revisions can be made directly in the text and the changes can be synchronized or not.…”
Section: Interactivity and Collaborationmentioning
confidence: 99%
“…Based on the survey analyses, they affirmed that wikis are a solid technology elected and recognizable for a significant part of users. Gomes and Sousa (2013) introduced some activities to Information System Management classes whose the objective was to validate the desired Wiki outcomes for teaching and learning process. They concluded that teaching and learning through wikis platforms can contributes greatly to the development of teamwork processes, self-organization, integrity, and openness.…”
Section: Wikis and Higher Educationmentioning
confidence: 99%